Postharvest losses of fruit and vegetables during retail and in consumers’ homes: Quantifications, causes, and means of prevention - Porat, Ron; Lichter, Amnon; Terry, Leon A.; Harker, Roger; Buzby, Jean (Elsevier, 2018)
The issue of food loss and waste (FLW) reduction has recently achieved much public attention as part of worldwide efforts to combat global hunger and improve food security. Studies conducted by various international and national organizations led by the FAO indicated that about one third of all food produced on the planet and about a half of all fruit and vegetables (F&V) are lost and not consumed. FLW occurs during five key stages of the food supply chain: agricultural production, postharvest handling and storage, processing, distribution, and consumption. Large portions of FLW in developed countries occur during retail and consumption, and are largely related to logistic management operations and consumer behaviors. In light of the great importance of FLW reduction, the United Nations set up in September 2015 an ambitious goal to halve per capita global food waste by 2030, and this decision was adapted by the US Federal Government, the EU Parliament, and many other countries. This first Adel Kader review article is dedicated to the subject of F&V losses during retail and consumption, and contains the following chapters: 1) Introduction of the problem of global food losses; 2) Quantifications of F&V losses during retail and consumption in the UK, US and other countries; 3) Causes and consumer decisions related to F&V wastage; 4) Emerging new technologies for prevention of F&V losses, including advances in logistics and cold chain management, retail packaging and technological innovations; 5) Other means to reduce F&V losses, including consumer awareness campaigns, advertisement of home storage instructions and policy and legislative measures. Due to the great importance of reducing F&V losses, we encourage postharvest researchers to become more engaged with logistics and food supply-chain operations, and to conduct multidisciplinary research incorporating consumer behavior studies into postharvest research.
Keywords: Food loss; Fruit; Postharvest; Retail; Vegetables; Waste